Crosstalk between the innate immune system and selective autophagy in hepatitis B virus infection - Miyakawa, Kei; Jeremiah, Sundararaj Stanleyraj; Ogawa, Michinaga; Nishi, Mayuko; Ohnishi, Makoto; Ryo, Akihide (Autophagy, 2022)
Although the involvement of macroautophagy/autophagy in hepatitis B virus (HBV) infection has become clearer recently, whether selective autophagy plays an important role in suppressing HBV remains uncertain. We recently found that LGALS9 (galectin 9) is an interferon (IFN)-inducible protein involved in the suppression of HBV replication. Expression of LGALS9 in HBV-infected cells causes the formation of cytoplasmic puncta that degrade the HBV core protein (HBc) in conjunction with RSAD2/viperin, another IFN-inducible protein. LGALS9 binds to HBc via RSAD2 and promotes the autoubiquitination of RNF13 (ring finger protein 13) to recruit SQSTM1/p62, resulting in the formation of LC3-positive autophagosomes that degrade HBc. Both LGALS9 and RSAD2 are encoded by IFN-stimulated genes that act synergistically to induce HBc proteolysis in HBV-infected hepatocytes in an IFN-dependent manner. These results reveal a crosstalk mechanism between the innate immune system and selective autophagy during viral infection.